On the Treatment of Acute Poisoning With Paracetamol - A. Yu. Simonova; M. M. Potskhveriya; M. V. Belova; K. K. Ilyashenko; V. V. Kulabuhov; N. Y. Stolbova; A. E. Klyuev (Неотложная медицинская помощь)
BACKGROUND Currently, despite the optimization of diagnostic methods in order to predict the development of liver damage, improvement of treatment protocols, paracetamol poisoning is a serious problem in medicine, being the most common cause of acute liver failure worldwide.AIM OF STUDY To determine the indications for the use of acetylcysteine in paracetamol poisoning and evaluate the effectiveness of the 21-hour protocol for its administration.MATERIAL AND METHODS We examined 20 patients with acute paracetamol poisoning (15 women and 5 men), the median age was 21.5 (19.8–32.3) years. ALT and AST were assessed during the entire period of stay in the hospital, the time period from the moment of taking paracetamol to hospitalization and the beginning of the administration of ACC, the concentration of paracetamol in the blood, and mortality. According to the level of ALT and AST in the blood, the patients were divided into 2 groups: Group I consisted of 14 patients, in whom the concentration of ALT and AST during the entire observation period did not exceed 50 U/L; in Group II (6 patients), an increase in the level of ALT and AST in the blood of more than 50 U/L was observed. To assess the risk of liver lesion, the Rumack-Matthew nomogram was used. To compare the concentrations of paracetamol in the blood of patients, the paracetamol index was used.RESULTS It was found that in 10 patients with a high risk of liver damage, who were treated with a 21-hour regimen of ACC administration, no hepatotoxic effect was found. The use of ACC according to a 21-hour protocol in patients with initially elevated ALT and AST levels of more than 50 U/L (n = 4) (25%) led to a rapid positive dynamics of laboratory and clinical parameters. It was found that in 2 patients, despite the introduction of ACC, the development of liver damage was observed. At the same time, the level of paracetamol in their blood was 6.6 and 10.6 fold higher than the “therapeutic” line of the nomogram, and the time from the moment of taking the drug to the beginning of the administration of ACC was 8 and 20 hours. High risk factors for the development of hepatotoxic effect in case of paracetamol poisoning are the time range from the moment of taking the drug to the beginning of the administration of ACC and the value of the paracetamol index.CONCLUSION Indications for the use of acetylcysteine in acute poisoning with paracetamol is a high risk of liver damage. Its criteria are high doses, increased concentrations of ALT and AST when patients are admitted to the hospital; if it is possible to determine the concentration of paracetamol in the blood, an increase in the value of the paracetamol index is more than 1. The use of a 21-hour protocol of intravenous administration of acetylcysteine is effective in case of paracetamol poisoning and its early use in the complex of treatment almost always prevents the development of acute liver failure.